Serum Amylase Level in Acute Organophosphorus Compound Poisoning in a Tertiary Level Hospital (Journal of Medicine, 2021)
Background: Organophosphorus compound (OPC) poisoning is an important clinical problem in the developing world and kills an estimated 3,00,000 people every year. In spite of high case fatality rate early and proper management is crucial to save the lives and alleviate the sufferings. Amylase level is an important biochemical marker, which is closely related to severity of acute OPC poisoning. Therefore, to assess Serum amylase level in acute organophosphorus compound poisoning in a tertiary level hospital was the objective of the study.Methods: This research was a hospital based descriptive cross-sectional study and was conducted at the inpatient department of Medicine in Dhaka Medical College. 50 Patient admitted in medicine department due to OPC poisoning and evidenced by history taking and physical examination were included in the study. Ethical issues were ensured properly. After written informed consent history and physical examination were done. Rest of the data were collected by interviewing each patient or from attendant of the patient by using a semi-structured questionnaire. Scoring of the severity were done by researcher himself by Peradeniya Organophosphorus Poisoning (POP) scale (Score range 0 to 11). Values of amylase level were collected from patient record file. All the Data was analysed by computer with the help of SPSS 16.Results: Out of a total of 50 patients, 24 (48%) were males and 26 (52%) were females. OPC poisoning was most frequent (52%) in age group 21-30 years. Mean age was 23.96 ± 6.071 SD. 96% (48) study population were Muslim and rest 4 % (2) were Hindus with diverse occupation. 86% population came from rural area whereas only 14% population reside in urban area. Among them suicidal attempts were seen significantly which was 96% and rest of them were accidental ingestion. Amylase level estimation were done in each case and 32 % (16) patient had elevated amylase level (>100U/L) and 68% (34) patient had amylase level within normal limit. Mean amylase concentration was 62.2U/L (SD±18.77) and among the 16 patients who had elevated serum amylase level mean concentration was 376.56U/L (SD±266.124). Mean amylase level differed significantly between these two groups (p value < 0.0001) estimated by one way ANOVA. Spearman Correlation and One way ANOVA both showed significant association between severity (assessed by POP scale) and elevated level of serum amylase (p value